2006
DOI: 10.5713/ajas.2006.601
|View full text |Cite
|
Sign up to set email alerts
|

Study on Extraction of Mucopolysaccharide-protein Containing Chondroitin Sulfate from Chicken Keel Cartilage Electrophoresis

Abstract: The objective of this study was to investigate technical methods for extraction of mucopolysachharide-protein containing chondroitin sulfate from keel cartilage of chickens. The chemical composition of chicken keel cartilage was determined. For the preparation of mucopolysaccharide-protein from lyophilized chicken keel cartilage, hot water extraction and alcalase hydrolysis methods were examined. Results showed that the optimum condition of hot water extraction was incubation for 120 min with a yield of 40.09%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
2
5
2
3
Order By: Relevance
“…The chemical compositions of chicken keel cartilages were determined and shown in Table 1. The content of the basic components similar to the analysis results of Shin et al [4].…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The chemical compositions of chicken keel cartilages were determined and shown in Table 1. The content of the basic components similar to the analysis results of Shin et al [4].…”
Section: Methodssupporting
confidence: 87%
“…The result in Table 4 showed that moisture content 7.4 % is similar to the result of the study of S.C. Shin [4], protein content 6.05 % is lower, the content of carbohydrate is similar. By HPLC method, researched CS obtained the purity of 80.45 % ( Figure 5) with the average molecular weight ( w ) of 159.53kDa by GPC (Table 5 and Figure 6).…”
Section: Physicochemical and Chemical Characteristics Of The Obtained Cssupporting
confidence: 79%
“…Keel cartilage CS-peptide has been extracted by several researchers (Garnjanagoonchorn et al, 2007;Luo et al, 2002;Shin et al, 2006). However, these authors have not provided basic analytical data (e.g.…”
Section: Chemical Analysis Of Cs-peptidementioning
confidence: 99%
“…Nakano et al (1998) incubated bovine nasal cartilage in 0.1 mol/L sodium acetate at pH 4.5 and 37 C and reported that approximately 80 g/100 g of total uronic acid was released from the tissue. Nakano et al (2000) then reported extraction of more than 70 g/100 g of total uronic acid by incubating bovine nasal cartilage in acidified water at pH 4.5 and 37 C. Shen and Ghosh (2004) incubated bovine tracheal cartilage in 0.1 mol/L calcium acetate, pH 4.5 at 37 C and reported that the GAG-peptide extracted is substantially free of contaminating DNA. There are, however, few reports of extraction of GAG from chicken tissues by using the autolysis technique.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation